Hubungan Keikutsertaan Kelas Ibu Hamil dengan Tingkat Kecemasan Ibu Hamil Menghadapi Persalinan di Desa Margaluyu Kecamatan Campaka - Melati Yuliandari; Fauzya Wikawati; Yeti Hernawati (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2024)
Health services for pregnant women including antenatal class health counseling are one of the activities that can be used to reduce anxiety in facing childbirth and provide motivation and education to pregnant women so that mothers have knowledge and insight about pregnancy and childbirth. The purpose of this study was to determine the relationship between class participation of pregnant women and the level of anxiety of pregnant women facing childbirth in the village of Margaluyu, Campaka District. The type of research was analytic observational with a cross-sectional design involving 55 respondents by accident, where the sample was determined by taking respondents who happened to be there and available, the type of primary data was carried out in Margaluyu Village, Campaka District using the Chi-Square Test. The results of the study showed it was found that 40 people (72.7%) attended classes for pregnant women and 15 people (27.3%) did not take classes for pregnant women, and 10 pregnant women with mild anxiety (18.2%), pregnant women with moderate anxiety were 4 people (7.3%) and pregnant women who did not feel anxious were 41 people (74.5%) and the results of the Chi-Square analysis were obtained, namely p = 0.001 ( p = <0.05). The conclusion in this study is that there is a relationship between class participation for pregnant women and the level of anxiety of pregnant women facing childbirth in Margaluyu Village, Campaka District.